Peningkatan Minat dan Hasil Belajar Materi Getaran dan Gelombang pada Siswa Kelas VIII D melalui Model Group Investigasi - Rina Guswati (Universitas Batanghari Jambi, 2022)
The lecture technique that does not vary used is not suitable for students because it is less fun and makes learning meaningless and this low learning outcome occurs in students of SMPN 10 Muaro Jambi. The low student learning outcomes are caused by the lack of accuracy in using the learning model. The investigative group learning model can be an alternative to fun learning, improving learning outcomes and making students build their own knowledge.